How to establish business process management with employee's help? A new methodology (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
By understanding the importance and achievements of managing business processes in practice, the desire and consequently the demand for guidance, guidelines, and a roadmap to guide organizations in this direction to have an integrated and unified set increases. The concept of business process management methodology is explicitly presented to address this issue. This article reviews and compares existing methodologies. Also, it includes evaluating the usability and actual use of the new methodology and then reviewing and evaluating the new methodology (D & R[1] BPM[2] METHODOLOGY) through interaction with a large group of managers and consultants with experience working in this field. Our findings show that this group of people is very welcome in the proposed methodology and consider it more comprehensive and complete than other methodologies. It should also be noted that our first proposal for such a methodology is based on the experience we have encountered from a large number of business process management projects over the past 12 years, from 2007 to the present. In summary, we have proposed 6 phases that apply to each organization and company. This methodology has already been used in more than 30 projects to deploy business process management.In this paper we have some part:Context(explain about how organized paper), 2. Objective and Theoretical Background (view objects and different issues), 3. Method (quantitative questionnaire containing),  4. Results and 5. Conclusions (the benefit of using the D & R Methodology). [1] Daliri and Ramezani[2] Business Process Management